1989
DOI: 10.1093/brain/112.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Patients With Clinically Isolated Lesions of the Type Seen in Multiple Sclerosis

Abstract: This study reports the performance on psychometric tests of a group of 48 patients with clinically isolated lesions of the type seen in multiple sclerosis (optic neuritis, brainstem and cord lesions). The cognitive functions studied were: 'IQ deficit', verbal and visual memory, abstracting ability, visual and auditory attention, and naming ability. The presence of brain pathology was investigated by means of magnetic resonance imaging (MRI). A group of 46 patients with rheumatic and neurological conditions not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 0 publications
3
41
0
3
Order By: Relevance
“…They found that severe fatigue in MS is associated with a reduction in glucose metabolism in the prefrontal cortex, adjacent white matter and basal ganglia, and concluded that fatigue may result from demyelination of the frontal white matter. This is consistent with the previously reported correlation between fatigue and impaired cognition in the early stages of MS. 21 The possibility that fatigue may indicate primary demyelination or axonal damage in the cerebrum has implications for the treatment of MS. If this is confirmed by further research, severe fatigue may itself become an indication for the treatment of MS in order to minimize further CNS damage.…”
Section: Mechanism Of Fatiguementioning
confidence: 99%
“…They found that severe fatigue in MS is associated with a reduction in glucose metabolism in the prefrontal cortex, adjacent white matter and basal ganglia, and concluded that fatigue may result from demyelination of the frontal white matter. This is consistent with the previously reported correlation between fatigue and impaired cognition in the early stages of MS. 21 The possibility that fatigue may indicate primary demyelination or axonal damage in the cerebrum has implications for the treatment of MS. If this is confirmed by further research, severe fatigue may itself become an indication for the treatment of MS in order to minimize further CNS damage.…”
Section: Mechanism Of Fatiguementioning
confidence: 99%
“…33 Slowed cognitive processing is present early in the disease and can be seen in people with clinically isolated syndromes -a single episode of demyelination in one area of the CNS, eg optic neuritis or brainstem or spinal cord syndrome -with asymptomatic lesions elsewhere in the brain on MRI. 34 In people with established MS, around 40 per cent have cognitive abnormalities. 35 Risk factors for impaired cognitive function in MS are age greater than 40 years, low premorbid intelligence or educational attainment, and depression.…”
Section: Cognitive Disordersmentioning
confidence: 99%
“…Nevertheless, the effect of cognitive impairment on everyday life activities, employment status, and social relationships is considerable (Amato et al, 1995;Rao et al, 1991b). Cognitive impairment may occur in the earliest stages of the disease (Achiron & Barak, 2003;Callanan et al, 1989;Deloire et al, 2005;Feinstein et al, 1992;Glanz et al, 2007) even in patients with clinically isolated syndrome (CIS) (Achiron & Barak, 2003;Feuillet et al, 2007;Glanz et al, 2007;Potagas et al, 2008). Cognitive deficits may develop independently from physical disability particularly in the early stage of the disease and in patients with benign MS (Feuillet et al, 2007;Glanz et al, 2007;Portaccio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%